Czechosłowackie podróże w czasie – od filmowej lekcji przyrody do normalizacyjnej zwariowanej komedii - Guzek, Mariusz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
Czechoslovakian film fantasy has its own canon comprised of various works, the successes of which were recorded by press industries around the world. They picked up various threads, but the most interesting one seems to be the theme of time travel, as represented by three films: A Journey to the Beginning of Time (1955), I Killed Einstein, Gentlemen (1969) and Tomorrow I’ll Wake Up and Scald Myself with Tea (1977). They were produced in different production conditions and placed in different genre assumptions, and they referred to the tradition of science fiction developed by popular literature in different ways. The text tries to define their status as part of the achievements of national cinematography, indicate structural components, and briefly discuss their reception, both critical and audience.